The effect of remimazolam on postoperative memory retention and delayed regeneration in breast surgery patients: Rationale and design of an exploratory, randomized, open, propofol-controlled, single-center clinical trial. Issue 48 (3rd December 2021) - Shirozu, Kazuhiro; Nobukuni, Keiko; Funakoshi, Kouta; Nakamura, Taizo; Sumie, Makoto; Higashi, Midoriko; Yamaura, Ken
Abstract: Background: Remimazolam, a benzodiazepine ultra-short-acting sedative, has been used in general anesthesia since August 2020. It is used in awake surgeries that require awakening the patient in the middle of the surgery because of its rapid awakening effect as well as antagonistic interactions. If remimazolam has associated anterograde amnesia similar to benzodiazepines, it will have a positive effect on preventing psychological trauma. However, to our knowledge, the effect of remimazolam on anterograde amnesia has not been previously examined. Methods/design: The aim of this exploratory, open, propofol-controlled, single-center, randomized clinical trial is to examine the effect of remimazolam on postoperative memory retention and delayed regeneration. Seventy patients undergoing breast surgery will be included in the study. The patients will be randomly assigned to receive propofol or remimazolam as sedatives during surgery. The primary endpoint is the number of posters patients remember 24 hours after surgery (among 4 posters shown after awakening from anesthesia) as an assessment of anterograde amnesia. Secondary endpoints are retrograde amnesia, dose of analgesic given from the time the patient returns to the ward until 24 hours after surgery, immediate postoperative pain numerical rating scale scores, and pain numerical rating scale scores 24 hours after leaving the operating room. Recruitment will take place between October 2021 and March 2022 to achieve the target sample size. Discussion: To our knowledge, this is the first trial designed to examine the effects of remimazolam on postoperative memory retention and delayed regeneration in patients undergoing breast surgery. Trial registration: This clinical trial was registered at the University Hospital Medical Information Network (UMIN) Center on September 28, 2021 (UMIN-CTR: UMIN000045593). Abstract : Supplemental Digital Content is available in the text